2007
DOI: 10.1002/humu.20510
|View full text |Cite
|
Sign up to set email alerts
|

Involvement ofDFNB59 mutations in autosomal recessive nonsyndromic hearing impairment

Abstract: In a consanguineous Turkish family, a locus for autosomal recessive nonsyndromic hearing impairment (ARNSHI) was mapped to chromosome 2q31.1-2q33.1. Microsatellite marker analysis in the complete family determined the critical linkage interval that overlapped with DFNB27, for which the causative gene has not yet been identified, and DFNB59, a recently described auditory neuropathy caused by missense mutations in the DFNB59 gene. The 352-amino acid (aa) DFNB59 gene product pejvakin is present in hair cells, sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 11 publications
1
56
0
Order By: Relevance
“…otoacoustic emissions was also observed in human patients with DFNB59 mutations [89][90][91][92] , indicating that DFNB59 mutations primarily or secondarily also affect cochlear amplification. A recent study has identified a role of pev jakin in the proliferation of peroxisomes in hair cells and SGNs in response to loud sound 93 .…”
Section: Glutamate Excitotoxicitymentioning
confidence: 85%
“…otoacoustic emissions was also observed in human patients with DFNB59 mutations [89][90][91][92] , indicating that DFNB59 mutations primarily or secondarily also affect cochlear amplification. A recent study has identified a role of pev jakin in the proliferation of peroxisomes in hair cells and SGNs in response to loud sound 93 .…”
Section: Glutamate Excitotoxicitymentioning
confidence: 85%
“…Allele binning was performed with the Excel 2000 (Microsoft) macro linkage designer developed by van Camp and coworkers (37), and we checked Mendelian inheritance of alleles with PedCheck 1.0 software (http://watson.hgen.pitt.edu) (38). Multipoint LOD scores were calculated with the GeneHunter, version 2.1 release 5, program in the easyLINKAGE software package (39).…”
Section: Statisticsmentioning
confidence: 99%
“…Allele binning was performed with the Excel 2000 (Microsoft) macro linkage designer developed by van Camp and coworkers (31), and we checked Mendelian inheritance of alleles with PedCheck 1.0 software (http:// watson.hgen.pitt.edu/register/docs/pedcheck.html) (32). Multipoint lod score and haplotype analysis was performed with GeneHunter, version 2.1 release 5, in the easyLINKAGE software package (33) and Haplopainter software (haplopainter.sourceforge.net/html/index.html).…”
Section: Figurementioning
confidence: 99%